Enhanced Device Efficiency of Bilayered Inverted Organic Solar Cells Based on Photocurable P3HTs with a Light‐Harvesting ZnO Nanorod Array. Issue 6 (8th November 2013) - Kim, Sehwan; Koh, Joo Hwan; Yang, Xu; Chi, Won Seok; Park, Chihyun; Leem, Jung Woo; Kim, Byeonggwan; Seo, Seogjae; Kim, Yuna; Yu, Jae Su; Kim, Jong Hak; Kim, Eunkyoung
<x xml:space="preserve">Abstract</x> Periodically patterned zinc oxide nanorod (P‐ZnO NR) layers are directly prepared from a pre‐patterned ZnO seed layer using a polydimethylsiloxane (PDMS) elastomeric stamp and then applied in inverted organic photovoltaic devices (IOPVs). The IOPV is assembled with a hydrothermally grown zinc oxide nanorod patterns with a (100) preferential crystal orientation as an electron transport buffer layer (ETBL) and photoactive bilayer consisting of methacylate end‐functionalized poly(3‐hexylthiophene) (P3HT‐MA), phenyl‐C60‐butyric acid methyl ester (PC60BM) and indene‐C60 bis‐adduct (IC60BA). In te IOPVs, the P‐ZnO NR is found to induce efficient light harvesting and the photocrosslinkable P3HTs afford solution‐processed bilayer architecture in IOPVs to show improved device stability and performance (PCEmax= 5.95%), as the bilayered structure allowed direct exciton splitting, thus reducing the charge recombination.